An exploration of the impact of injury on motivation in Mixed Martial Artists: A qualitative study - Driemeyer, Jayde (The IIE, 2020)
There is much research on motivation in Martial Artists (MMA) and injury in MMA respectively, there is a gap in literature addressing the possible relationship between the two. Leaving the phenomenon impact of injury, a regular occurrence in the sport, on the motivation of the athletes, and their experience unclear; this needs to be addressed and explored to establish a better understanding of the phenomenon for athletes, coaches and researchers. The study aims to investigate the ways injury impacts an MMA athlete’s motivation, specifically to determine whether a link between injury and motivation in MMA athletes exists by explaining which motivational factors influence the athlete’s decision to return to the sport and what role support holds. A semi-structured interview was done over Zoom on a sample of 3 MMA athletes with 5 or more years of experience who have experienced an injury. The results suggested there is a link between injury and motivation it was initially assumed this relationship would illicit a negative affect with athletes becoming less inclined to participate, however, this was not the case. While a link is established more research is needed to develop a more concrete understanding of its nature.
Keywords: Motivation; Mixed Martial Arts (MMA); Mixed Martial Artists; Injury